Omega-3 for the Prevention of Alcohol Use Disorder Relapse: A Placebo-Controlled, Randomized Clinical Trial - Pauluci, Renata; Noto, Ana Regina; Curado, Daniela Fernandez; Siqueira-Campos, Miguel; Bezerra, Andréia Gomes; Galduróz, José Carlos Fernandes (Frontiers in Psychiatry, 2022)
Background Recent studies have sought to identify the possible benefits of the intake of omega-3, an important component of neuronal membranes, for the treatment of alcohol use disorder. Aim The objective of the present study was to evaluate whether omega-3 supplementation is protective against alcohol use disorder relapse after hospital discharge. Methods A randomized, double-blind, placebo-controlled study was carried out with severe alcohol dependence. Male inpatients were randomized to treatment with omega-3 (n = 59) or placebo (n = 52) for 3 months, participants were assessed after discharge at 1 month (T1), 2 months (T2), 3 months (T3), and 6 months (T4) with assessments made using self-report instruments. The primary outcomes were the possible reduction with assessments made using self-report instruments. The primary outcomes were the possible reduction in the number, intensity of relapses, amount of consumption in each relapse and number of days of consumption during relapses; as secondary outcomes were assessed symptoms of anxiety, depression, degree of dependence, compulsion, and craving. Results The groups were similar regarding consumption amount parameters and propensity to relapse; however, an effect of treatment with omega-3 was found on the number of days of drinking at 2 months [B = 0.65 (0.09; 1, 21), p = 0.01] and 3 months [B = 2.6 (1.61; 3.58), p < 0.001] after discharge, favoring the intervention group. The effect was not maintained at follow up of 6 months. No differences were found in psychiatric symptoms and severity of addiction. Conclusion Despite the major limitations of the present study, the group that received omega-3 had a lower number of days of consumption of standard doses of alcohol in the evaluations of 60 and 90 days after discharge. More robust studies are needed to confirm or refute these findings. Brazilian Registry of Clinical Trials: n° RBR-48mkgz7 (URL: https://ensaiosclinicos.gov.br/rg/RBR-48mkgz7).